Caracterização da qualidade de água e sedimento relacionados com a ocorrência de plantas aquáticas em cinco reservatórios da bacia do rio Tietê - Cavenaghi, A.l. [UNESP]; Velini, E.d. [UNESP]; Galo, M.l.b.t. [UNESP]; Carvalho, F.t. [UNESP]; Negrisoli, E. [UNESP]; Trindade, M.l.b.; Simionato, J.l.a. (Sociedade Brasileira da Ciência das Plantas Daninhas, 2003)
This research is part of a project aiming to develop aquatic plant integrated management programs in five reservoirs of the Tietê watershed (São Paulo, Brasil) used to produce electric energy. The occurrence of aquatic plants was correlated to water and sediment composition. Water and sediment samplings and field evaluations were performed in June 2001 (drought season), October/November of 2001 (start of rainy season) and February/March 2002 (end of rainy season). Water samples were used to estimate the transmission or extinction of light from 190 to 900 nm by 1 m-thick water columns. To better understand and register (in digital pictures) the problems encountered with the formation of sediment banks and aquatic plants, all the reservoirs were overflown using a helicopter, on June 4th and 5th. The results allowed to conclude that the occurrence of submersed plants, mainly Egeria densa and Egeria najas, is highly dependent on water transparency and light transmission. The higher turbidity and content of suspended solids, as well as the lower light transmission change the frequency of submersed plants. Promissão and Nova Avanhandava reservoirs were the most infested with submersed plants. The occurrence of marginal and floating plants is highly dependent on the formation of sediment banks. Barra Bonita, Bariri and Ibitinga reservoirs were the most infested with marginal and floating plants. P and N concentrations, turbidity and the contents of suspended solids were reduced by the downstream movement along the sequence of reservoirs (Barra Bonita => Bariri => Ibitinga => Promissão => Nova Avanhandava).

Este trabalho é parte integrante de um projeto de pesquisa que tem por objetivo o desenvolvimento de programas de manejo integrado de plantas aquáticas em cinco reservatórios da bacia do rio Tietê, usados na produção de energia elétrica. A ocorrência de plantas aquáticas foi correlacionada com a qualidade da água e do sedimento. Amostragens de água e sedimento e levantamento de plantas foram realizados em junho de 2001 (estação seca), outubro/novembro de 2001 (início da estação chuvosa) e fevereiro/março de 2002 (final da estação chuvosa). Amostras de água foram utilizadas para estimar a transmissão ou extinção de luz em comprimentos de onda de 190 a 900 nm para colunas de água de 1 m de profundidade. Para melhor entendimento e registro (em fotos digitais) dos problemas com formação de bancos de sedimento e plantas aquáticas, todos os reservatórios foram sobrevoados, usando um helicóptero, nos dias 4 e 5 de junho de 2001. Os resultados permitiram concluir que a ocorrência de plantas submersas, destacando-se Egeria densa e Egeria najas, foi a mais dependente da transparência da água e transmissão de luz. A maior turbidez e sólidos suspensos contidos e a menor transmissão de luz alteram a freqüência de plantas submersas. Os reservatórios de Promissão e Nova Avanhandava foram os mais infestados com plantas submersas. A ocorrência de plantas marginais e flutuantes é muito dependente da formação de bancos de sedimentos. Os reservatórios de Barra Bonita, Bariri e Ibitinga foram os mais infestados com plantas marginais e flutuantes. A concentração de fósforo e nitrogênio, a turbidez e os sólidos suspensos foram reduzidos com o deslocamento ao longo da seqüência de reservatórios no rio Tietê (Barra Bonita => Bariri => Ibitinga => Promissão => Nova Avanhandava).
Caracterization of water quality and sediment related to the occurrence of aquatic plants in five Tietê waterhed reservoirs
Keywords: water quality; aquatic plant; sediment; reservoir; qualidade de água; planta aquática; sedimento; reservatório